(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the phenomenon of gamification in the modern educational paradigm from a scientific and pedagogical perspective. The history of the formation of gamification, its relevance in the educational process, motivational and cognitive impact, as well as didactic possibilities are highlighted. The article argues that gamification is not just playing games, but a systematic pedagogical technology that serves educational purposes [1]. At the same time, the limitations encountered in its implementation, including excessive reliance on external stimuli, infrastructure problems, teacher digital competence and issues related to the assessment system, are also considered [2]. In conclusion, the need to use gamification as a tool that increases educational effectiveness, ensures active student participation, and strengthens person-centered education is emphasized.